Perbandingan Hasil Belajar Menggunakan Model Discovery Learning dengan Problem Based Learning Mata Pelajaran Aqidah Akhlak Kelas XI MA Abu Darrin Bojonegoro - Badi’ Rohmawati, Ulva; Muthi’udin, Ahmad; Nur Kholisah, Siti (Institut Agama Islam Al-Hikmah Tuban, 2023)
Abstract: Based on the pre-research conducted at MA Abu Darrin Bojonegoro, it is known that the implementation of the Aqidah Akhlak learning process is still monotonous, the teacher does not vary with interesting learning models so that it does not increase student motivation in learning, therefore students are less attentive, less active in the learning process. To overcome this, improvements are needed in the learning process, one of which is by using discovery learning and problem based learning models. So that the formulation of the problem in this study is whether there are differences in student learning outcomes between the discovery learning model and problem based learning. This study aims to determine how big the difference in student learning outcomes between discovery learning and problem-based learning on the subject of aqidah morality, the material of social behavior for teenagers in class XI MA Abu Darrin Bojonegoro. This research is a quasi-experimental design research. The research was conducted in class XI which was divided into experimental class and control class. In the experimental class a discovery learning model is applied and in the control class a problem based learning model is applied. Data collection techniques using objective tests, interviews, observation and documentation. The data analysis technique used is descriptive analysis, homogeneity test, normality test, and hypothesis testing. Based on the results of the analysis and discussion of the research data, the results of descriptive analysis obtained the average value of the two classes, namely the experimental class using the discovery learning model, the results before treatment (pretest) were 60,00 after being treated (posttest) was 80,58 and the control class using a problem based learning model, the result before treatment (pretest) was 59,41 after being given treatment (posttest) was 81,76. Based on the results of inferential analysis using an independent sample t test with a significance level of 0.05, a significant value of 0.542 was obtained, so it can be concluded that Ho is accepted and H1 is rejected because the value of sig > (0.542 > 0.05). Thus, it can be concluded that there is no difference between the use of discovery learning models and the use of problem based learning models on student learning outcomes in Aqidah morality subjects in class XI MA Abu Darrin Bojonegoro. Keywords: Discovery Learning Model, Problem Based Learning Model, Learning Outcomes.